Robot Pembawa Barang Berbasis Mikrokontroler ATMega8535L Dengan Pengendali Remote - Muhammad Taufik; Erma Triawati (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Goods Carriers Robot based Microcontroller ATMega 8535L with Remote control is a tool that has function to transport goods from one place to another is controlled automatically. The goal is to alleviate human work, especially the work of carrying in shopping center. The tool consists of several circuit blocks. There are the battery circuit to output 3V, 5V, and 12V, motion sensor, transmitter module 27 MHz, receiver module 27 MHz, and the limit switch as an input, the controller circuit using ATMega 8535L and gearbox motor circuits as output. The automation of robot movement with transmitter and receiver modules with a range of up to 540 cm to regulate the movement of the robot in four directions, namely forward, backward, right, and left. When the presence of human movement to the distance 1.9 m in front of the robot, the motion sensor will detect it, the robot will stop moving. The total of heavy loads can be carried by the robot up to 660 gr limited by limit switches.Keywords: Microcontroller ATMega 8535L, Motion Sensor, Limit switch, Transmitter 27 MHz, Receiver 27 MHz.